EAPH-07. CHILDREN'S BRAIN TUMOUR DRUG DELIVERY CONSORTIUM. Issue 2 (22nd June 2018) - Rahman, Ruman; Grundy, Richard; Campbell, Emma; Brem, Henry; Pearl, Monica; Green, Jordan; Janowski, Miroslav; Cohen, Kenneth; Walczak, Piotr; Warren, Katherine; Lowis, Stephen; Mullen, Alexander; et al.
Abstract: INTRODUCTION: There is an urgent need to expedite the development of new or repurposed drugs for children's cancer. An additional challenge in the developing brain is to ensure the drug is delivered to the tumour at therapeutic and non-toxic concentrations for sufficient duration to achieve the biological effect. Children's brain tumours account for over 20% of childhood cancers and differ significantly in their biological characteristics from their adult counterparts. METHODS: The authors participated in an international CNS drug delivery workshop funded by the charity Children with Cancer UK in February 2016, where different experimental techniques aimed at optimising CNS drug delivery in children's brain tumours were discussed. RESULTS: The workshop was reported by e-cancer (http://ecancer.org/journal/10/full/630-highlights-of-children-with-cancer-uk-s-workshop-on-drug-delivery-in-paediatric-brain-tumours.php ; http://ecancer.org/conference/831-drug-delivery-in-paediatric-brain-tumours.php ). We were encouraged to develop a proposal to establish an international research consortium to raise awareness and promote collaboration in the field. This is now funded for two years by Children with Cancer UK. The Children's Brain Tumour Drug Delivery Consortium seeks to strengthen collaborative developments by working closely with the international children's brain tumour community, encouraging and facilitating discussions between a multi-disciplinary network of clinicians and researchers within pharma and academia as well as a range of funders and stakeholders. As of January 2018, we have 92 individuals from 11 nations registered as members, with diverse stakeholders represented by academics, clinical academics, charities, public/patient groups, industry and regulatory bodies. CONCLUSION: We present this abstract to the ISPNO conference to promote this initiative in America, widening our invitation for collaborators to join the consortium.